A synthetic biological quantum optical system. Issue 27 (29th June 2018) - Lishchuk, Anna; Kodali, Goutham; Mancini, Joshua A.; Broadbent, Matthew; Darroch, Brice; Mass, Olga A.; Nabok, Alexei; Dutton, P. Leslie; Hunter, C. Neil; Törmä, Päivi; Leggett, Graham J.
Abstract : Strong coupling between plasmon modes and chlorins in synthetic light-harvesting maquette proteins yields hybrid light–matter states (plexcitons) whose energies are controlled by design of protein structure, enabling the creation of new states not seen under weak coupling. Abstract : In strong plasmon–exciton coupling, a surface plasmon mode is coupled to an array of localized emitters to yield new hybrid light–matter states (plexcitons), whose properties may in principle be controlled via modification of the arrangement of emitters. We show that plasmon modes are strongly coupled to synthetic light-harvesting maquette proteins, and that the coupling can be controlled via alteration of the protein structure. For maquettes with a single chlorin binding site, the exciton energy (2.06 ± 0.07 eV) is close to the expected energy of the Q y transition. However, for maquettes containing two chlorin binding sites that are collinear in the field direction, an exciton energy of 2.20 ± 0.01 eV is obtained, intermediate between the energies of the Q x and Q y transitions of the chlorin. This observation is attributed to strong coupling of the LSPR to an H -dimer state not observed under weak coupling.